2019
DOI: 10.1590/0034-7167-2018-0306
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in the climacteric of nurses working in primary care

Abstract: Objective: to evaluate the quality of life of primary care nurses in the climacteric. Method: A cross-sectional descriptive-analytic study, performed with 98 female nurses, aged 40-65 years, using the WHOQOL-Bref questionnaire. Results: the worst level of quality of life was observed for professionals aged 50-59 years, non-white, specialists, divorced or widowed, with children, a lower income, with another employment relationship, a weekly workload of more than 40 hours, who consumed alcoholic beverages week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
3
1
0
8
Order By: Relevance
“…In terms of nurses' quality of life, current study revealed that quality of life was lower in older nurses who were working rotated shift and those having higher years of experience, which is in line with previous studies that found a significant association between quality of life and age (Albuquerque et al., 2019) and years of experience (Tessy, 2014). Thus, leaders should be conscious to work‐related factors that lead to reduce quality of life which include worked shift and years of experience.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of nurses' quality of life, current study revealed that quality of life was lower in older nurses who were working rotated shift and those having higher years of experience, which is in line with previous studies that found a significant association between quality of life and age (Albuquerque et al., 2019) and years of experience (Tessy, 2014). Thus, leaders should be conscious to work‐related factors that lead to reduce quality of life which include worked shift and years of experience.…”
Section: Discussionsupporting
confidence: 91%
“…Where married professionals or those in a stable relationship had a higher WHQ score on somatic symptoms, sexual and global functioning on the WHQ, in addition to a lower SF-36 score on vitality. This corroborates with other studies, which point to a correlation between a better quality of life in women who had a partner to the detriment of those who declare themselves single or divorced 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Married professionals or those in a stable relationship scored higher on WHQ somatic symptoms and sexual and global functioning domains, in addition to a lower SF-36 score on vitality. These findings corroborate other studies that point to a correlation between a better quality of life in women living with a partner compared to those who declare themselves single or divorced [ 32 ].…”
Section: Discussionsupporting
confidence: 91%